Tratamiento contable de los inventarios y la razonabilidad de los estados financieros en las empresas del sector agrícola - Calle Ávila, Janeth Alexandra (2022)
The general objective of this research work is to evaluate the adequate accounting treatment of Inventories and its impact on the reasonableness of the Financial Statements of machinery trading companies to the agricultural sector. The research focuses on the application of International Accounting Standard 2 referring to Inventory, as a standard that issues the main guidelines in the accounting treatment of these current assets. The issue is highly relevant due to the importance of keeping the book values adjusted to fair net values. It is an investigation with a qualitative and quantitative approach, of a non-experimental and transversal type, using in the same way a field, descriptive and analytical investigation…………